Impact of food price changes on household welfare in Ghana - Minot, Nicholas; Dewina, Reno (International Food Policy Research Institute, 2013)
In this paper, we explore the distributional impact of higher maize, rice, and food prices in Ghana and analyze the robustness of those results to changes in several key assumptions.